The Relationship Between Innovation and Technology That Influence Airport Service Quality Based on Innovating PortalFit Malaysia for Future: Malaysia - Amir, Ahmad Fitri; Abdul Satar, Nurul Hasanah; Mohd Ali, Nur Syahirah; Abd Rahman, Rosliza (Multidisciplinary Applied Research and Innovation, 2023)
PortalFit is an innovative airport passengers’ check-in equipment that benefits public health and safety. The product can provide greater peace of mind and convenience among airport passengers due to its capability of simplifying check-in procedures and reducing physical contact. These features are practically significant in times of the health crisis like COVID-19 pandemic as airport passengers are required to deal with additional check-in procedures incorparating the COVID-19 Standard Operating Procedures (SOPs). PortalFit is a single equipment that is able to perform five functions in a single check-in process; body temperature scan, passport verification for blacklist status, visa status, boarding pass print, and luggage drop.